Psychometric validation of Filipino versions of the survey of attitudes toward statistics and attitudes toward research for nursing students - Almazan, Joseph U.; Jabonete, Fritz Gerald; Adolfo, Cris S.; Albougami, Abdulrhman S. B.; Tariga, Jose Arnold; Cruz, Jonas Preposi (Jurnal Ners, 2025)
Introduction: Despite the recognized importance of assessing nursing students' attitudes toward statistics and research, no validated instruments exist specifically for the Filipino context. This study aimed to evaluate the psychometric properties of the Filipino adaptations of the Survey of Attitudes toward Statistics (SATS-F) and Attitudes toward Research (ATR-F) scales. Methods: A quantitative cross-sectional survey design, using convenience sampling, was employed to collect data from August to October 2022. Participants were Filipino nursing students taking nursing research and statistics courses who were at least 18 years old. Participants with >10% incomplete data on any instrument were excluded. Results: Descriptive statistics showed mean scores ranging from 4.45 to 6.10 for ATR-F items and 2.88 to 5.55 for SATS-F items. A strong content validity was demonstrated, with S-CVI/Ave values of 0.94 for ATR-F and 0.98 for SATS-F. Principal Component Analysis (PCA) showed 75.3% of the cumulative explained variance for ATR-F and 61.9% for SATS-F. Pearson correlation analysis further supported construct validity, revealing a significant positive relationship (r = 0.50, p < 0.001) between ATR-F and SATS-F, which indicates a strong association between nursing students' attitudes toward research and statistics. Internal consistency reliability was established, with Cronbach's alpha coefficients of 0.87 for ATR-F and 0.90 for SATS-F. Conclusions: SATS-F and ATR-F possess sound psychometric properties, rendering them reliable tools for assessing Filipino nursing students' attitudes toward statistics and research. Educators and researchers can use these culturally adapted and validated instruments to develop targeted interventions to enhance nursing students' preparedness for research-informed practice.